100 GHz Reflectometer for Sensitivity Analysis of MEMS Sensors Comprising an Intermediate Frequency Six-port Receiver - Linz, Sarah; Oesterle, Florian; Talai, Armin; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2015)
Due to the growing market for Micro Electro Mechanical Systems (MEMS), especially for the application in mobile electronic devices like cameras, phones or tablet computers, cost and time efficient test and evaluation systems are required for the production process. This work presents a novel measurement setup for MEMS microphones, that allows an inline, contactless evaluation of the microphones' mechanical sensitivity at an early stage of the manufacturing process. A heterodyne receiver with a Six-port demodulator is deployed for displacement detection with micrometer resolution. Since the Six-port demodulator allows very high sampling rates only limited by the analog-to-digital converter, short measurement times can be achieved.
elib2cris::1512001600,linz2015
Keywords: MEMS; Six-Port; Microwave Interferometer; W-band; Contactless Testing; Pull-in; Mechanical Sensitivity

A 1.16 pJ/bit 80 Gb/s 2¹¹-1 PRBS generator in SiGe bipolar technology - Radwan, Ahmed; Talai, Armin; Weigel, Robert; Kissinger, Dietmar (9th European Microwave Integrated Circuit Conference (EuMIC), 2014)
A 211-1, 80Gb/s pseudo-random bit sequence (PRBS) generator, employing parallel architecture is presented. The generator is optimized to provide a high bit rate as well as a long sequence length without any need of inductive peaking for a lower power consumption, compared to PRBS generators reported in literature. The PRBS generator consists of two parallel complementary rows of linear feedback shift registers (LFSR), operating up to 40Gb/s, where the generated PRBS from each are multiplexed to provide a bit-rate of double the clock frequency, reaching up to 80Gb/s. The clock distribution network was carefully optimized for a reduced amplitude and phase error to push the boundaries of the maximum achievable bit-rate. The PRBS generator is capable of generating bit-rates ranging from 10Gb/s up to 80Gb/s, with a power consumption of 576 mW to 1 W. The circuit is manufactured in an 0.35 μm SiGe-Bipolar technology with an ft of 200 GHz.
elib2cris::1512001600,gharib2014b

A Coplanar Waveguide Resonator Based In-Line Material Characterization Sensor for Bulk and Metallized Dielectrics - Talai, Armin; Gold, Gerald; Frank, Martin; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (Frequenz, 2016)
Microwave Materials such as Rogers RO3003 are subject to process-related fluctuations in terms of the relative permittivity and dielectric loss. The behavior of high frequency circuits like patch-antenna arrays and their distribution networks is dependent on the effective wavelength. Therefore, fluctuations of the complex permittivity will influence the resonance frequency and beam direction of the antennas. This paper presents a grounded coplanar waveguide based sensor, which can measure the complex permittivity at 77 GHz, as well as at other resonance frequencies, by applying it on top of the manufactured depaneling. The relative permittivity of the material under test (MUT) is a function of the resonance frequency shift and the dielectric loss of the MUT can be determined by transmission amplitude variations at the resonances. In addition, the sensor is robust against floating ground metallizations on inner printed circuit board layers, which are typically distributed over the entire surface below antennas. Furthermore, the impact from conductor surface roughness on the measured permittivity values is determined using the Gradient Mode
lhft_intern.bib::talai2016a

A Finite 3D Field Simulation Method for Permittivity Gradient Implementation of a Novel Porosification Process in LTCC - Talai, Armin; Steinhäußer, Frank; Schmid, Ulrich; Weigel, Robert; Bittner, Achim; Kölpin, Alexander (IEEE MTT-S International Microwave Symposium, 2013)
High frequency substrates show a manifold variety of complex permittivities for different applications. Recent research results demonstrated the possibility of local decrease of the permittivity on LTCC by chemical etching processes, which enables the design of high quality antennas on LTCC. This paper shows a novel approach on the determination of the quantitative reduction of the effective permittivity by scanning electron microscope analyses in combination with finite 3D field simulations of the resulting inhomogeneous material. By the characterization of two different porosified LTCCs it could be shown that this process is suitable for direct antenna integration on glass-ceramic substrates with enhanced values of relative permittivities.
elib2cris::1512001600,talai2013a
Keywords: Field simulation; LTCC; local reduction of permittivity; porosification; wet chemical etching; inhomogeneous substrate; permittivity gradient

A Grounded Coplanar Waveguide Resonator Based In-Line Material Characterization Sensor - Talai, Armin; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (German Microwave Conference (GeMIC), 2016)
Microwave Materials such as Rogers RO3003 are subject to process-related fluctuations in terms of the relative permittivity. The behavior of high frequency circuits like patchantenna arrays and their distribution networks is dependent on the effective wavelength. Therefore, fluctuations of the relative permittivity will influence the resonance frequency and antenna beam direction. This paper presents a grounded coplanar waveguide based sensor, which can measure the relative permittivity at 77GHz, as well as at other resonance frequencies, by applying it on top of the manufactured depaneling. In addition, the sensor is robust against floating ground metallizations on inner printed circuit board layers, which are typically distributed over the entire surface below antennas.
elib2cris::1512001600,talai2016
Keywords: Antenna Array; Grounded CoplanarWaveguide; Differential Frequency; Electromagnetic Simulation; Floating Ground; Material Characterization; Relative Permittivity

A Method for the Determination of the Complex Permittivity by Detuned Ring Resonators for Bulk Materials up to 110 GHz - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (International Journal of Microwave and Wireless Technologies, 2015)
elib2cris::1512001600,talai2015

An Accurate Free Space Method for Material Characterization in W-Band Using Material Samples with Two Different Thicknesses - Lau, Isabella; Frank, Martin; Shi, Kilin; Lurz, Fabian; Talai, Armin; Weigel, Robert; Kölpin, Alexander (European Microwave Conference (EuMC), 2018)
This paper presents an accurate free space method for material characterization eliminating the problem of the required precise orientation between the material and the antennas and expanding the unambiguous range for electrical thick samples. It includes theoretical considerations and measurement results of four different materials. Overall, a maximum measurement uncertainty of 0.0153 for the relative permittivity and 0.001 for the loss tangent in the W-band can be achieved. Depending on the variation of the material’s thickness, the implemented setup changes lead to an reduction of the measurement uncertainty of 8 to 58%.<br
Keywords: permittivity; dielectric materials; microwave measurement; materials nondestructive testing

A New Approach For A Dual-Polarized Low Cost Patch Antenna With Low Cross- Polarization, High Bandwidth And High Isolation - Stöckle, Andreas; Lutz, Steffen; Talai, Armin; Fischer, Georg (IEEE-APS Topical Conference on Antennas and Propagation in Wireless Communications, 2014)
In this paper a new approach for a dual- polarized broadband patch antenna is presented. A novel feeding approach enables a high -10dB band- width up to 21 % as well as an isolation more than -29 dB. The realized antenna gain is > 6 dBi in the frequency range of 1320 MHz to 1680 MHz. Addi- tional, due to the re ector shaping, a low back ra- diation is achieved. Since standard components and FR4 material are used, the antenna concept enables an e ective low cost antenna production.
elib2cris::1512001600,stoeckle2014

A Permittivity Characterization Method by Detuned Ring-Resonators for Bulk Materials up to 110 GHz - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (44th European Microwave Conference (EuMC), 2014)
An accurate characterization of microwave materials is essential for reliable high frequency circuit design. This paper presents a measurement setup, which enables a quick and accurate determination of the relative permittivity of dielectric bulk materials up to 110 GHz. A ring-resonator is manufactured on a well characterized substrate dealing as reference resonator. The Material Under Test (MUT) is placed on top of the ring, which increases the effective permittivity and therefore introduces a shift of the resonance frequency of the resonator. Electromagnetic field simulations with different heights and relative permittivities of the MUT provide a lookup table for the measured resonance frequencies. The functionality of the proposed measurement setup is validated by measurement results of different MUTs.
elib2cris::1512001600,talai2014f
Keywords: Bulk material; detuned resonator; frequency shift; material characterization; permittivity; ring resonator

A Resonant Substrate Integrated Waveguide Measurement System for True Relative Permittivity Extraction of PCB Materials up to 90 GHz - Lau, Isabella; Michler, Fabian; Talai, Armin; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Microwave Workshop Series on Advanced Materials and Processes (IMWS-AMP), 2018)
This paper presents a resonant measurement method based on substrate integrated waveguide cavities for determination of the true relative permittivity of a PCB material. The sensor is manufactured on the unknown PCB material and in contrast to existing, comparable methods, the extraction process takes into account the metal roughness. The proposed method does not require any reference materials or sensors on different PCB thicknesses. This paper contains considerations regarding the design and simulation as well as measurement results of the sensor system. To validate the measurement system, the extracted relative permittivity values of the RO4350B substrate over the frequency range of 10 GHz to 90GHz are presented.<br

A Semi Double-Ridged quasi TE-Waveguide based Microwave Bulk Material Characterization System - Talai, Armin; Mann, Sebastian; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Microwave Symposium (IMS), 2015)
Accurate microwave material characterization is essential for reliable high frequency circuit design. Therefore, various characterization techniques have been developed, comprising advantages and drawbacks for the respective conditions. In this paper, a material characterization system is presented, which enables a broadband measurement for both dielectric loss and relative permittivity of bulk substrates with variant geometrical dimensions. A semi double-ridged waveguide is used to measure the introduced phase shift and dampening due to a strip of material, allowing a combined evaluation of the complex permittivity by measurement and simulation.
elib2cris::1512001600,talai2015a
Keywords: Material Characterization; Phase Measurement; Ridged Waveguide; Relative Permittivity

A simplified equivalent model for microwave characteristics of porosified LTCC - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (XXXIth URSI General Assembly and Scientific Symposium (URSI GASS), 2014)
High frequency materials show a manifold variety of complex permittivities for different applications. Recent research results demonstrated that porosification of Low Temperature Cofired Ceramics (LTCC) represents a new manufacturing technology, which enables local selective reduction of the relative permittivity. The permittivity gradients were measured and subsequently modeled to perform electromagnetic field simulations. The results of the complex CAD model are used, to create a simplified equivalent model, which is suitable for rapid RF circuit design on porosified LTCC. Since substrate properties vary between circuit components, the substrate-dependency on the lumped elements of the transmission line model is considered. It is shown that the introduced porosification gradient can be considered for network-based SPICE simulations on porous LTCC.
elib2cris::1512001600,talai2014b

A Tank Level Sensor Based on Six-Port Technique Comprising a quasi-TEM Waveguide - Mann, Sebastian; Lindner, Stefan; Linz, Sarah; Barbon, Francesco; Talai, Armin; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2014)
Robust tank level monitoring is an important issue in chemical and process industry and a challenging task if high accuracy has to be reached. The proposed sensor structure consists of a quasi-TEM mode waveguide on the one hand and an interferometric Six-Port receiver structure on the other hand. The waveguide structure itself in combination with the liquid to be monitored acts as a reflection phase shifter. By superposing the reflected and the transmitted electromagnetic wave within a passive structure, the relative phase between both signals can be accurately obtained by means of the Six-Port principle. Thus, a change of the liquid level is directly related to the relative phase shift monitored by the Six-Port interferometer. In contrast to antenna based tank level sensors, the hereby presented system concept makes use of a novel waveguide structure. therefore, it is not sensitive to multi-target scenarios and multipath propagation.
elib2cris::1512001600,mann2014
Keywords: Six-Port; Interferometer; tank; level monitoring; parallel plate waveguide; RADAR; microwave measurement

Broadband Characterization of Launchers and Transitions - Talai, Armin (2016)
Characterizing material properties with a high degree of precision requires very accurate sensors, which means that the properties of the sensor itself must also be accurately characterized. Simulation allows the properties of elements of the test equipment to be calculated in isolation or be integrated into the simulation model for the test set-up, and allows the design of the sensor to be optimized. This article will demonstrate how CST® STUDIO SUITE® was used to simulate and optimize a coaxial-microstrip transition for a material characterization measurement system, including the effect of the probes themselves, and analyze the effect of surface roughness on the properties of the sensor.
elib2cris::1512001600,talai2016b
Keywords: Launchers; Transitions; Material Characterization; Surface Roughness

Efficient radar front-end implementation in LTCC multilayer cavity technology - Talai, Armin; Weigel, Robert; Kölpin, Alexander (Workshop on Recent Progresses in mmW Multilayer Circuit and System Design and Packaging (MCM/SoP), 2017)
Low Temperature Cofired Ceramics (LTCC) is a high-frequency material type that is suitable for multilayer structures and applications. Since its relative permittivity is usually in the region of 6 to 10, microwave structures can be designed in a space-saving way. The implementation of patch-antennas on LTCC, such as radar antennas at 77 GHz, require a lower permittivity in order to achieve a desirable efficiency and focusing capability. Therefore, this presentation will focus on a novel method of using the multilayer capabilities of LTCC in order to decrease the local permittivity below the antennas. Before sintering, carbon inserts are embedded on inner layers below the antennas by using an Nd:YAG laser. It will be demonstrated that these inserts are burned out completely during sintering and the cavity remains. The process requires an adaption of the sintering profile in order to reduce the sinking of the substrate in the middle of the cavity. Within this presentation, the achievable improvements on antenna beams will be presented by comparative simulation results of 77 GHz antennas with and without the embedded cavity. Furthermore, presented measurement results will verify the effects of the cavit
Keywords: Multilayer; Cavity; LTCC; Antenna

Electromagnetic analysis of conductor track surface roughnesses from 1 GHz to 110 GHz - Talai, Armin; Gmeiner, Björn; Wegener, Carsten Moritz; Roosen, Andreas; Kölpin, Alexander; Steinhäußer, Frank; Deisinger, Ulrike; Bittner, Achim; Schmid, Ulrich; Weigel, Robert (Electromagnetics in Advanced Applications (ICEAA), 2014 International Conference on, 2014)
Conductor tracks comprise a frequency dependent attenuation of electromagnetic waves, since with increasing frequency the current flow is displaced to the near surface region due to the skin effect. Therefore, the effective length of the conductor is increased by the surface roughness, while its effective cross-section is decreased by current displacement, both leading to higher metallization loss. In this paper, surface topographies of typical conductor materials were recorded by confocal microscopy and rebuilt as 3D CAD models. Subsequent electromagnetic simulations reveal the influence due to roughness on high frequency characteristics for physical vapor deposited, thick film and photochemically etched microstrips.
UnivIS-Import:2015-04-17:Pub.2014.tech.IMMD.lsinfs.electr

Electromagnetic Analysis of Fringed Microstrip Lines on Dense and Porosified LTCC - Talai, Armin; Gmeiner, Björn; Weigel, Robert; Kölpin, Alexander (Computer Simulation Technology - European User Conference, 2014)
The shapes of microstrip line edges comprise a large influence on various microwave circuitry characteristics. Therefore, the edges of thick film gold conductor tracks have been analyzed by scanning electron microscopy and rebuilt in 3D according to the measured fringing dimensions of co-fired and post-fired conductor tracks on Low Temperature Cofired Ceramic (LTCC). Subsequent time-domain field simulations with CST from 0 GHz to 110 GHz reveal the influence of fringed conductor edges on metallization loss, scattering parameters and the effective permittivity, which will be presented. Simulations of fringed Microstrips on porosified LTCC are compared to the dense case. It is shown that fraying has less impact on porosified LTCC, since the relative permittivity at the near-surface region is strongly reduced by the introduced ai
elib2cris::1512001600,talai2014e

Electromagnetic Analysis of Fringed Microstrip Lines on Porosified LTCC - Talai, Armin; Steinhäußer, Frank; Gmeiner, Björn; Bittner, Achim; Rüde, Ulrich; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (Electromagnetics in Advanced Applications (ICEAA), 2013 International Conference on, 2013)
Recent investigations demonstrated that porosification of LTCC enables a local modification of material properties, in particular of the effective permittivity. These studies revealed that the electric field strength is highest at the lower conductor track edges on the porosified substrate. The local field strength peaks cause substantial influence on the effectiveness of permittivity reduction due near-surface material abrasions. In this paper, the influences of these randomly fringed boundaries on electromagnetic properties are investigated for different degrees of fraying. The gained results are compared to measured screen print edges by scanning electron microscope image analysis of co-fired and post-fired gold conductors, and will contribute for reliable circuit design on porous LTCC in the future. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lsinfs.electr_6
Keywords: cofired; Conductor edge; field simulation; fringed microstrip; inhomogeneous substrate; LTCC; porosification; reduction of permittivity; structural modeling

Electromagnetic Field Analysis of Porosified LTCC - Talai, Armin; Weigel, Robert; Kölpin, Alexander (Computer Simulation Technology - European User Conference, 2013)
elib2cris::1512001600,talai2013

Electromagnetic field analysis with advanced structural modeling of microstrips on porosified LTCC - Talai, Armin; Weigel, Robert; Kölpin, Alexander; Gmeiner, Björn; Rüde, Ulrich; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich (Microwave Conference (EUMC), 2013 European, 2013)
Recent investigations demonstrated that porosification offers the possibility of high quality antenna integration on LTCC by local reduction of the relative permittivity. In order to take advantage of this technology, further research for the deposition of conductors on porosified areas has to be done. Since the near-surface material removal is strong, conductors are expected to penetrate substantially into the porosified substrate. In this paper a new, randomized structural modeling technique of porosified LTCC is presented, which is based on scanning electron microscope imaging. Finite 3D field simulations, performed with this model, show the electromagnetic effects of different vertical microstrip positions on the effective permittivity and the corresponding scattering parameters. © 2013 European Microwave Association.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lsinfs.electr_9
Keywords: Field simulation; inhomogeneous substrate; LTCC; porosification; reduction of permittivity; structural modeling

Embedded Cavity based Dielectric Loss Measurements for LTCC Substrates up to 110 GHz - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Schwanke, Dieter; Rittweg, Thomas; Weigel, Robert; Kölpin, Alexander (IEEE MTT-S International Conference on Numerical Electromagnetic and Multiphysics Modeling and Optimization (NEMO), 2015)
In literature there exists manifold techniques for measuring the permittivity of substrates. Printed circuit board (PCB) based methods like dielectric resonators are in general limited to determine the absolute value of the complex permittivity since e.g. a half wave resonator only provides information on the electrical length, which is inversely proportional to the square root of the absolute value of the permittivity. Additionally, dielectric loss measurements are more difficult, expensive and often limited to discrete frequency points due to resonance based measurement principles. In this paper, a PCB based dielectric loss measurement system is presented, operating from a few GHz up to 110 GHz, which is based on a differential measurement of a microstrip line on dense low temperature cofired ceramics (LTCC) and a microstrip on a LTCC layer with an embedded cavity. The cavity reduces the dielectric loss of the transmission line by replacing a certain amount of substrate with air. Subsequent electromagnetic time domain field simulations allow the dielectric loss assignment over the measured transmission frequency range.
elib2cris::1512001600,talai2015b
Keywords: Dielectric Loss; Differential Amplitude; Embedded Cavity; LTCC; Material Characterization

Erforschung geeigneter Modellierungstechniken für 3D Hochfrequenzstruktursimulationen zur Bestimmung der effektiven relativen Permittivität für porosizierte LTCC Substrate - Talai, Armin; Kölpin, Alexander; Weigel, Robert (U.R.S.I. Kleinheubacher Tagung 2012, 2012)
Die relative Permittivität eps_r eines keramischen Hochfrequenz-Substrates wie LTCC (engl.: Low Temperature Cofired Ceramics) kann durch nasschemische Ätzverfahren lokal reduziert werden, indem ein Teil des dielektrischen Verbundwerkstoffes herausgelöst wird. Mit dieser Methode soll die Abstrahlcharakteristik von Patchantennen-Arrays, wie bspw. für KFZ-Radare der nächsten Generation, optimiert werden. In diesem Beitrag werden dazu erforderliche 3D-Hochfrequenzstruktursimulationsansätze vorgestellt, welche einen ersten Eindruck für das Potential über die Manipulationsmöglichkeiten von ǫr durch diese neue Technologie liefern. Die Vorstellung einer messtechnischen Validierungsmöglichkeit mittels Ringresonatoren rundet die erzielten Simulationserkenntnisse ab.
elib2cris::1512001600,talai2012

Field Distributions and Effective Permittivities Along Microstrip Structures on Homogeneous and Inhomogeneous Substrates up to 110 GHz - Talai, Armin; Weigel, Robert; Kölpin, Alexander (European Microwave Conference Workshops, 2013)
Rohde und Schwa
elib2cris::1512001600,talai2013d

Graphical based characterisation and modelling of material gradients in porosified LTCC - Steinhäußer, Frank; Talai, Armin; Steiger-Thirsfeld, A.; Kölpin, Alexander; Weigel, Robert; Bittner, Achim; Schmid, Ulrich (Journal of the European Ceramic Society, 2013)
The chemical composition of LTCC (low temperature cofired ceramics) allows the local implementation of air into the sintered substrates by a selective wet chemical etch process. Therefore, LTCC substrates with areas of low as well as of high permittivity can be created without a material combination. The presented graphical method of material component contrast images enables the evaluation of the most important material properties after their local porosification which are their component distribution, their porosification gradient and their residual bearing surface. The graphical method, including focused ion beam and scanning electron microscopy analyses, is applied to different commercially available LTCC types having two porosification states each. The derived mathematical models, suitable for finite element method implementation, allow the characterization of the effective permittivity reduction while keeping a maximum residual surface area for e.g. metallization purposes. The shape of the optimum material distribution function features an ‘air pocket’ of small width and a depth being dependent on the application specific operating frequency.
elib2cris::1512001600,steinhaeusser2013a
Keywords: porosity; dielectric properties; glass ceramics; graphical method; wet etching

In-Line Material Characterization Sensors Operating at 10 GHz and 77 GHz - Frank, Martin; Talai, Armin; Weigel, Robert; Kölpin, Alexander (Asia Pacific Microwave Conference (APMC) 2017, 2017)
This paper describes the design of two sensors for the in-line material characterization of bulk and metallized dielectrics around 10,GHz and 77,GHz in order to determine the relative permittivity of RF substrates. The sensors are based on a resonant grounded coplanar waveguide structure and can be applied on top of a material under test. The shift in the resonance frequency between loaded and unloaded resonator is evaluated by 3D full wave simulations in order to determine the relative permittivity. The basic sensor structure is improved for the in-line characterization of printed circuit boards by a clearance of the resonator area and the filling of the air gaps. Measurements with different MUTs were performed with both sensors followed by the evaluation of the relative permittivity. The results are in good agreement with the expected permittivity values and show high reproducibilit
Keywords: Material Characterization; Relative Permittivity; Grounded Coplanar Waveguide

Modellierung nass-chemischer Porosizierverahren auf LTCC für elektromagnetische Hochfrequenz Feldsimulation - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (Mikrosystemtechnik Kongress (MST), 2015)
elib2cris::1512001600,talai2015c
Keywords: LTCC

Permittivity Reduction and Surface Modification by Porosification of LTCC - Steinhäußer, Frank; Talai, Armin; Kölpin, Alexander; Weigel, Robert; Bittner, Achim; Schmid, Ulrich (Ceramics International, 2016)
The wet-chemical porosification of low temperature co-fired ceramics is investigated with respect to the resulting permittivity reduction and surface modification. Therefore, four commercially available tapes were treated and characterized by measuring the detuning of a resonator as well as by chromatic white light and scanning electron microscopy analyses. The results show a technically relevant permittivity reduction of about 15 to 18% measured at a frequency of 44 GHz. Thereby, the vertical distribution of the air, embedded by the porosification is of high influence. The achievable reduction in permittivity strongly counteracts the surface quality, which is necessary for applying high quality metallization lines.
elib2cris::1512001600,steinhaeusser2016a
Keywords: LTCC; porosification

Poröses LTCC als Substratmaterial für Höchstfrequenzradarsensoren - Bittner, Achim; Steinhäußer, Frank; Talai, Armin; Kölpin, Alexander; Weigel, Robert; Rittweg, Thomas; Schwanke, Dieter; Sandulache, Gabriela; Hansal, Wolfgang; Schmid, Ulrich (International Conference on Electromagnetics in Advanced Applications (ICEAA), 2015)
elib2cris::1512001600,bittner2015

Porösizierte Glaskeramik-Substrate für die Radarsensorik - Talai, Armin; Bittner, Achim; Steinhäußer, Frank; Schmid, Ulrich; Kölpin, Alexander; et al. (Automobil-Sensorik 2, 2018)
Für Komfortfunktionen und aktive Sicherheitsfunktionen werden in modernen Fahrzeugen Radarsensoren im freigegebenen Frequenzband zwischen 77 GHz und 79 GHz benötigt. Um einen langzeitstabilen Betrieb bei gleichzeitig geringer Baugröße der Radarsensoren zu gewährleisten, müssen robuste Materialsysteme mit geeigneten dielektrischen Eigenschaften im Bereich der Aufbau- und Verbindungstechnik verwendet werden. Kommerzielle LTCC (engl.: low temperature cofired ceramics) Glaskeramiksubstrate ermöglichen einen dreidimensionalen Aufbau bei hervorragenden Hochfrequenzeigenschaften. Um die Antennencharakteristik zu optimieren, wird ein Porösizier-Verfahren vorgestellt, um eine lokal reduzierte Permittivität zu erreichen. Dabei wird nasschemisch das Glaskeramikmaterial porösiziert, um oberflächennah eine Schicht mit reduzierter dielektrischer Konstante zu erzielen. Diese wird durch den Vergleich von Hochfrequenzmessungen mit numerischen Simulationsergebnissen bestimmt.<br
Keywords: Radar; Automotive; LTCC

Pulse Plated Silver Metallization on Porosified Low Temperature Co-fired Ceramics for High Frequency Applications - Steinhäußer, Frank; Talai, Armin; Sandulache, Gabriela; Weigel, Robert; Kölpin, Alexander; Hansal, Wolfgang; Bittner, Achim; Schmid, Ulrich (Microelectronics Reliability, 2016)
Advanced high frequency systems such as needed in modern radar applications, require high conductive metallizations as well as substrates with areas of variable permittivity. This paper presents the combination of the selective porosification technology of low temperature co-fired ceramics and electro pulse plated silver microstrip lines. By means of selective plating methods, line widths of 20 μm can be manufactured featuring low resistivity values down to 2.33 μΩ·cm, without detectable pore penetration. The substrate permittivity is measured facilitating a combined method of ring resonator detuning and 3D field simulations resulting in a reduction of 6.5% with a shift from approx. 7.52 to 7.03 at 66 GHz due to the porosification. As often outlined in literature the major challenge in using silver as a conductor lies in its high tendency of agglomeration and microstructural transformation especially in oxygen containing atmosphere even at low temperatures. Therefore, the effect of different temperature loads up to 500°C on the dc film resistivity are measured using the VAN DER PAUW technique and compared to scanning electron microscope analyses.
elib2cris::1512001600,steinhaeusser2016
Keywords: LTCC; porosification

Test of alternative LTCC manufacturing processes for HF applications with realistic modeling of thick film technologies - Talai, Armin; Donati, Giovanni; Weigel, Robert; Kölpin, Alexander (TuZ 2014 Testmethoden und Zuverlässigkeit von Schaltungen und Systemen, 2014)
elib2cris::1512001600,talai2014c

The impact of the material distribution of porousified LTCC on the effective permittivity investigated by finite 3D field simulation - Steinhäußer, Frank; Talai, Armin; Kölpin, Alexander; Weigel, Robert; Bittner, Achim; Schmid, Ulrich (Mikrosystemtechnik-Kongress (MST), 2013)
Apart from other advantages, such as its robustness, the high permittivity of LTCC (Low Temperature Cofired Ceramics) multi layer technology is one of the most important reasons why it is nowadays well established in high frequency devices and systems. However, reduced emission is not desired in every application. Antennas require a substrate with a low permittivity in order to achieve maximum emitter efficiencies. The chemical composition of LTCC allows the local introduction of air by means of a selective etch process. Due to this selective and diffusion controlled process the generated porousification is not homogeneous depending on the penetration depth. On the basis of measured lateral material distributions, the effect on the effective permittivity can be shown by performing 3D field simulations. The distributions are graphically derived from material cuts, which were realized by focused ion beam technology. From the complex trends, conclusion regarding the alteration of the inner chemical phase distribution as well as the quality and the bearing capability of the surface can be obtained.
elib2cris::1512001600,steinhaeusser2013

The Influence by Trapezoidal Conductor Shapes on Ring-Resonator based Material Characterization up to 110 GHz - Talai, Armin; Steinhäußer, Frank; Bittner, Achim; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (International Conference on Numerical Electromagnetic Modeling and Optimization for RF, Microwave, and Terahertz Applications, 2014)
Material characterization by ring-resonator based measurements is well established since the early 20th century. Since then, the demand on spectral complex permittivity characterizations of RF materials and dielectric covers at higher microwave frequencies rises. Nowadays, both free space applications, e.g. 77 GHz automotive radar systems, and dielectrics for microchip packages require accurate knowledge of the relative permittivity in order to optimize RF circuit designs. With increasing frequencies, the conductor shape of photochemically etched ring-resonators gets more influence on the effective ring radius, and therefore the measured resonance frequencies, which results in an error for the relative permittivity determination. This paper provides correction factors for the ring radii up to 110GHz, compensating the altered field distribution due to trapezoidal edges.
elib2cris::1512001600,talai2014a
Keywords: CAD Modeling; Effective Permittivity; Field Simulation; material characterization; Microstrip Structure; Ring-Resonator; Trapezoidal Conductor

The Six-Port Structure as a Precise Measurement Tool - A New Rise of an Old Concept - Kölpin, Alexander; Lindner, Stefan; Mann, Sebastian; Barbon, Francesco; Talai, Armin; Weigel, Robert (Kleinheubacher Tagung, 2013)
Six-Port Technique has been known in RF and microwave metrology since the early 1970s for vector network analysis and precise power measurements. Two decades later, the system has been proposed as a receiver for complex valued data reception. However, six-port technique has always been niche architecture, since the tremendous evolution in integrated circuit technology got more and more impact on high-end circuitry and measurement systems. But there are some special applications that can be very efficiently addressed by the six-port principle. In general, all scenarios where the interesting information is coded in signal power or can be translated in relative phase shifts are suitable for six-port systems, as this architecture offers superior phase resolution combined with low cost implementation. Furthermore, this principle can be used up to millimeter-wave frequencies and even higher. The reason is that the core functionality is realized only by passive transmission lines or waveguide structures featuring the interferometric part, and only diodes have to be used as monolithic components for the RF front-end. The information reconstruction is conducted in baseband by algorithms with very low complexity that can be run on a low power microcontroller and show only low latency of a few controller clock cycles. In this talk the newest results for applications addressed by six-port architecture for metrology will be presented. Besides very precise distance and angle measurements or vibration analysis, like heartbeat and breath rate detection, also new fields will be presented. One very promising approach is using the six-port technique for frequency analysis of a pulse-like microwave signal. Furthermore, the very first results in temperature measurements of a water basin by a six-port reflectometer will be shown.
elib2cris::1512001600,koelpin2013c
Keywords: Six-Port; Interferometer

Water Temperature Measurement by Microwave Six-Port Interferometry at 24 GHz - Talai, Armin; Mann, Sebastian; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks (WiSNet), 2014)
Microwave interferometry enables the possibility of highly accurate distance measurements by evaluating phase differences. The reflected power is a function of the effective radar cross-section, the measurement distance, and the attenuation in air. An irradiated plain water surface shows a temperaturedependent behavior by means of the reflected power. This is due to the fact that the complex permittivity of water, as well as the refractive index, strongly depends on the water temperature within the 24 GHz Industrial, Scientific and Medical (ISM) band. Consequently, the effective radar cross-section depends on the temperature as well. This paper describes a method of monitoring the water temperature as a side effect of an interferometric radar in Six-Port technology for water level measurements.
elib2cris::1512001600,talai2014